Las redes sociales y su papel en la transformación del consumo de maquillaje en Colombia: análisis del marketing de influencers (2025)
This research focused on analyzing how social media and influencer marketing have transformed purchasing habits and the relationship between brands and their consumers. In a highly competitive market, amidst a constantly evolving digital era, the study highlights the importance of continuous strategic adaptations that consider consumer behavior, explore modern digital trends, and optimize digital marketing strategies. The study covered the transition from traditional marketing to digital strategies, highlighting the role of influencers in them, as they not only generate trust, but also build digital communities that foster user loyalty to brands, establishing new interaction models.